2016
DOI: 10.1080/13102818.2016.1224978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study of intraspecific differences among Sauropus androgynus (L.) Merr. from Indonesia revealed by ITS region variability

Abstract: DNA sequence analysis of the nuclear ribosomal internal transcribed spacer (ITS) region was exploited for its applications in the authentication of Sauropus androgynus (L.) Merr. as raw-material herbal medicine and supplement. Leaf samples from 12 different geographic locations in Indonesia were collected. Twelve DNA sequences from the samples were analysed. The sequences were trimmed before sequence alignment. The sequences ranged from 626 to 664 bp in length after trimming. Based on the multiple sequence ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The DNA extraction from red ginger rhizome was performed using a specific set of reagents provided in the Nucleospin Plant II kit (Macherey-Nagel GmbH & Co. Germany) according to the previous research (Yunita et al 2016). A quantity of 100 milligrams of plant powder was put into a sterile tube.…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA extraction from red ginger rhizome was performed using a specific set of reagents provided in the Nucleospin Plant II kit (Macherey-Nagel GmbH & Co. Germany) according to the previous research (Yunita et al 2016). A quantity of 100 milligrams of plant powder was put into a sterile tube.…”
Section: Dna Extractionmentioning
confidence: 99%
“…The rhizome samples of red ginger were stored in a refrigerator set at a temperature of -20°C, following the methodology employed by Yunita et al (2016), until the commencement of the sample analysis procedure. The sample is cooled in this manner due to the inactivation of enzymes responsible for the degradation of nucleic acids and plant metabolites at a temperature of -20°C.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Hal ini diduga karena adanya kolom Nucleospin hijau pada kit. Nucleospin hijau ini terdiri dari kolom dengan fase diam silika yang dapat menahan DNA melalui terbentuknya ikatan antara DNA dengan silika (23).…”
Section: Hasil Dan Diskusiunclassified
“…Berdasarkan hasil optimasi penambahan PE dilakukan dua tahap elusi masing-masing 25 µl. Tahapan elusi yang dilakukan dua kali biasanya menghasilkan DNA yang lebih banyak dibandingkan dengan elusi yang dilakukan satu kali dengan volume total yang sama (17,23).…”
Section: Hasil Dan Diskusiunclassified
“…Unfortunately, few literature reviews have discussed methods for distinguishing S. androgynus cultivars based on their morphological characteristics. However, previous studies revealed that chromatography (Yunita et al, 2019) and several DNA-based methods such as random amplified polymorphic DNA (RAPD) (Yunita & Sulisetiorini, 2013) and sequencing of internal transcribed spacers (ITS) (Yunita et al, 2016) successfully discriminate between geographically sensitive S. androgynus cultivars.…”
Section: Introductionmentioning
confidence: 99%